IDENTIFICATION WHEAT GENOTYPES RESISTANT TO TAN SPOT PYRENOPHORA TRITICI-REPENTIS - Alma Kokhmetova; Makpal Atishova (Scientific Journal of Pedagogy and Economics, 2020)
Intensified wheat production, changes in cultural practices including shifts from conventional tillage to reduced tillage practices, and wheat monoculture involving cultivation of susceptible cultivars has resulted in development of tan spot to epidemic proportions in Kazakhstan. Pyrenophora tritici-repentis, causal agent of tan spot on wheat. In recent years, there has been increasing distribution and harmfulness of P. tritici-repentis on wheat. The aim of the study was to identify and select wheat germplasm resistant to tan spot P. tritici-repentis using molecular markers. The results of field evaluation showed resistant reaction to tan spot in 76 wheat varieties (68%). Molecular screening of wheat germplasm was carried out based on the reaction to the fungal inoculum and to hostspecific toxins (HST) produced by the P. tritici-repentis. The wheat germplasm insensitive to the toxins HST Ptr ToxA and Ptr ToxB was selected. As a result of molecular screening of 111 wheat genotypes using SSR marker Xfcp623 linked to insensitivity gene to the selective toxin Ptr ToxA of tan spot, 31 carriers of effective tsn1 gene were identified, which accounted for 27,9% of the genotypes studied. Ten samples of wheat (Jubileynaya 60, TOO11/TOOOO7, F3.71/TRM/VORONA/3/OC14, NANJTNG 82149 KAUZ, ECHA/LI115, Akmola 2, Kazakhstanskaya rannespelaya, Kazakhstanskaya 25, 428g/MK-122A and 190-Naz/GF55) are characterized with complex resistance to the races Ptr 1 and 5, as well as to 2 toxins (ToxA and ToxB) and to the Septoria nodorum blotch isolate SNB7k. 20 promising wheat lines resistant to tan spot were selected. These genotypes also showed a moderate and high level of field resistance and recommended to use in the breeding programs for resistance to tan spot.